A Case Series on Pregnant Patients with Mild Covid-19 Infection and Signs of Severe Placental Insufficiency - A. Ivert; C. Lindblad Wollmann; K. Pettersson (Case Reports in Obstetrics and Gynecology)
In this case series, we present five cases of pregnant women who sought medical attention for reduced fetal movements with an ongoing mild maternal Covid-19 infection at a Stockholm hospital in Spring of 2021. At the time of admission, the patients were in gestational week between 24+0 and 33+5. Abdominal ultrasound at the hospital showed no fetal movements, and cardiotocography (CTG) was pathological. All women delivered via cesarean section within 24 hours after admission. Placental pathology in all cases showed massive perivillous fibrin deposition and extensive histiocytic intervillositis. All placentas were Covid-19 polymerase chain reaction (PCR) positive. The infants were Covid-19 PCR negative. Consistent with other published case reports, we hypothesize that Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can affect the placenta resulting in massive perivillous fibrin deposition and histiocytic intervillositis leading to acute placental insufficiency and fetal hypoxia. The absence of intrauterine growth restriction also augments the theory of an acute onset of placental insufficiency due to the Covid-19 infection.